High-Resolution Microscopy And Microanalysis In Oral Biology And Dentistry. - Farid, C G (2003)
The oral region contains all types of mineralized tissues found in the body. Its nonnalmucosa lining exhibits a greater variation in histo-structure than found in the entire skin surface.